Analysis of Fire Simulation on Polyurethane Foam Using FDS in a University Meeting Room - Pratomo Setyadi; Dewi Muflihah (Journal of Applied Engineering and Technological Science (JAETS), 2023)
The polyurethane foam material is commonly used and marketed in two forms, namely flexible and rigid. Flexible foam is used as a cushion, with various applications for commercial products such as chair support. Therefore, this study aims to describe the occurrence of a fire situation in a university room filled with many polyurethane foam chairs. It also aims to provide awareness regarding potential flame hazards, by using a fire modelling method with FDS. The results showed that fires on PU foam materials produced a high HRR and a wide spread of flame and smoke. From this context, the harmful effects of the fire on the room occupants were emphasized. The results obtained are expected to support the theory of compartment fire, flame distribution in solid materials, PU Foam inferno behaviour, etc. It is also expected to provide additional fire protection and evacuation training for room occupants.